Cobalt nanoparticles embedded in N-doped carbon on carbon cloth as free-standing electrodes for electrochemically-assisted catalytic oxidation of phenol and overall water splitting. (December 2019) - Jia, Qianqian; Gao, Yuan; Li, Yang; Fan, Xiaobin; Zhang, Fengbao; Zhang, Guoliang; Peng, Wenchao; Wang, Shaobin
Abstract: Nowadays, environmental pollution and energy depletion are two important problems. In this work, we report the synthesis of cobalt nanoparticles (Co NPs) embedded in nitrogen doped carbon (NC) on carbon cloth (CC) by a two-step method to obtain Co@NC/CC and the application for both electrochemical assisted catalytic oxidation of phenol and electrochemical water splitting. An ultra-high activity could be obtained for the electrochemical catalytic oxidation of phenol, with the rate constant at 1.340 min −1, much larger than the catalytic oxidation process (0.21 min −1 ). Moreover, Co@NC/CC exhibits remarkable activities in both hydrogen evolution reaction (HER) and oxygen evolution reaction (OER). Especially, a very early HER overpotential of 118 mV is achieved at 10 mA cm −2 in 1 M KOH. The synergistic effect between Co and NC and the intimate interface are proposed to be the main cause of the enhanced activity. The free-standing and multi-functional Co@NC/CC electrode contains no noble metal, and should have great potential both in wastewater remediation and water splitting. Graphical abstract: Image 1